Production of white wine by Saccharomyces cerevisiae immobilized on grape pomace - Genisheva, Zlatina Asenova (2012)
White wine was produced with Saccharomyces cerevisiae cells immobilized on grape pomace, by natural adsorption. The support, the main solid waste from the wine industry, consisted of the skins, seeds and stems. Immobilization was tested using different media, namely complex culture medium, raw grape must and diluted grape must. Grape pomace was revealed to be an appropriate support for yeast cell immobilization. Moreover, grape must was shown to be the most suitable medium as immobilized cells became adapted to the conditions in the subsequent alcoholic fermentation in the wine-making process. The wines produced, either with immobilized cells or with free cells, were subjected to chemical analysis by HPLC (ethanol,glycerol, sugars and organic acids) and by gas chromatography (major and minor volatile compounds); additionally, colour (CIELab) and sensory analysis were performed. The use of immobilized systems to conduct alcoholic fermentation in white wine production proved to be a more rapid and a more efficient process, especially when large amounts of SO2 were present in the must. Furthermore, the final wines obtained with immobilized cells demonstrated improved sensory properties related to the larger amounts of ethanol and volatile compounds produced. The more intense colour of these wines could be a drawback, which could be hindered by the reutilization of the biocatalyst in successive fermentations.